Pengembangan Usaha Agribisnis Perdesaan (PUAP) Berbasis Produk Unggulan Kawasan Perdesaan (PURKADES) di Kecamatan Jatisrono Kabupaten Wonogiri - Hamidi, Muhammad Amin; Banowati, Eva (Geo-Image, 2021)
The basic problems faced by farmers are lack of access to sources of capital, marketing and technology, as well as weak farmer organizations. The objectives of this research are: 1) To find out what agribusiness enterprises are capable of becoming Jatisrono District Excellence. 2) Knowing what superior products are competitive in the market. 3) Assessing how the Rural Agribusiness Development (PUAP) can solve farmer problems. Statistical analysis techniques are descriptive statistics. Data analysis to support this research was also carried out by means of a SWOT analysis. There are 4 meanings in a SWOT analysis, namely; strengths (strengths), accessibility (weaknesses), opportunities (opportunities) and threats (threats). SWOT analysis to identify natural resources and human resource factors that affect superior products in rural areas. The strategic priorities produced in this study are Strengthening good communication with distributors to increase product sales, Strengthening relationships with suppliers of raw materials and labor for business continuity, Increasing synergy with the government through government programs that are in line with business actors, Strengthening marketing networks so that directly to the final level consumers, Optimizing capital and work experience and utilizing government equipment to improve product quality and quantity. Permasalahan dasar yang dihadapi petani adalah kurangnya akses kepada sumber permodalan, pemasaran dan teknologi, serta organisasi tani yang masih lemah. Tujuan dalam peneliian ini adalah : 1) Mengatahui usaha agribisnis apakah yang mampu menjadi Unggulan Kecamatan Jatisrono. 2) Mengetahui produk unggulan apakah yang mempunyai daya saing di pasaran. 3) Mengkaji bagaimanakah Pengembangan Usaha Agribisnis Perdesaan (PUAP) yang dapat mengatasi permasalahan petani. Teknik Analisis statistik deskriptif statistik. Analisis data untuk mendukung penelitian ini juga dilakukan dengan analisis SWOT. Ada 4 makna dalam analisis SWOT yaitu; strengths (kekuatan), weaknesses (kelemahan), opportunities (peluang) dan threats (ancaman). Analisis SWOT untuk identifikasi faktor SDA dan SDM yang mempengaruhi produk unggulan kawasan perdesaan. Prioritas strategi yang di hasilkan dalam penelitian ini yaitu Memperkuat komunikasi yang baik dengen distributor untuk meningkatkan penjualan produk, Memperkuat hubungan dengen pemasok bahan baku dan tenaga kerja untuk kebelangsungan usaha, Meningkatkan sinergi dengen pemerintah memalui program pemerintah yang sejalan dengan pelaku usaha, Memperkuat jaringan pemasaran agar langsung sampai ke konsumen tingkat akhir, Mengoptimalkan modal dan pengalaman bekerja serta memanfaatkan peralatan pemerintah untuk meningkatkan kualitas dan kuantitas produk.